Brazil's growth performance: Achievements and prospects - Luiz de Mello (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper reviews Brazil's growth performance over the last quarter of a century and discusses the main determinants of a pick-up in growth since the mid-1990s. Emphasis is placed on the policy pay-offs associated with a consolidation of macroeconomic adjustment, which is a pre-condition for sustained growth. Structural reform based on a liberalization of the county's trade and investment regimes have also generated productivity gains that have supported growth. The paper also discusses a number of policy challenges that will need to be addressed in the coming years to ensure that high growth can sustained over the longer term.
Keywords: O10; O20; O54; 330; Brazil; growth; structural reform; Wirtschaftswachstum; Brasilien